A New Lignan (Polonilignan) and Inhibitors of Nitric Oxide Production from Penicillium polonicum, an Endophytic Fungi of Piper nigrum. Issue 3 (9th February 2023) - Pal, Pragya Paramita; Begum, Sajeli A.; Basha, Ameer S.; Araya, Hiroshi; Fujimoto, Yoshinori
Abstract: Inhibiting nitric oxide (NO) or its production is found to be of therapeutic benefit. To discover natural small molecule inhibitors of NO production, a bioassay‐ and LC/MS‐guided chemical investigation was done on the metabolites of endophytic fungus isolated from fresh Piper nigrum fruits. The isolated pure strain was identified as Penicillium polonicum by 16S rDNA sequence comparison. The culture broth extract of P. polonicum (EEPP) exhibited a significant reduction of NO production (Griess method) in LPS‐stimulated RAW 264.7 cells ( P <0.0001). To understand the chemical constituents of bioactive EEPP, column chromatography and p‐TLC studies were carried out, which yielded eight pure compounds. They were characterised as botryosphaeridione (1 ), 3‐(3, 5‐di‐ tert ‐butyl‐4‐hydroxy)phenylpropionic acid (2 ), variabilone (3 ), 2, 4‐di‐ tert ‐butylphenol (4 ), indole‐3‐carboxylic acid (5 ), tyrosol (6 ), ethyl ferulate (7 ) and a new lignan (8 ) based on the spectral analysis. The structure elucidation of the new lignan, named polonilignan (8 ), was based on HR‐MS, 1 H‐ & 13 C‐NMR, H−H COSY, HSQC and HMBC spectra. Compounds 2, 4, 5 and 6 showed a significant decrease ( P <0.0001) in the production of NO in LPS‐induced RAW 264.7 cells. Tyrosol (6 ) and indole‐3‐carboxylic acid (5 ) controlled nitrite release with IC50 values of 22.84 and 55.01 μM, respectively. This is the first report of (i) P. polonicum as an endophytic fungus of pepper fruits, (ii) isolation of compounds 1 –8 except 6 from P. polonicum culture broth extract and (iii) NO inhibition effect of 2, 4, 5 and 6 . Abstract :